An extract from the frass of swallowtail butterfly (Papilio machaon) larvae inhibits HCT116 colon cancer cell proliferation but not other cancer cell types - Miho Nakano; Takuma Sakamoto; Yoshikazu Kitano; Hidemasa Bono; Richard J. Simpson; Hiroko Tabunoki (BMC Genomics, 2023)
Abstract Background The frass of several herbivorous insect species has been utilised as natural medicines in Asia; however, the metabolite makeup and pharmaceutical activities of insect frass have yet to be investigated. Oligophagous Papilionidae insects utilise specific kinds of plants, and it has been suggested that the biochemicals from the plants may be metabolised by cytochrome P450 (CYP) in Papilionidae insects. In this study, we extracted the components of the frass of Papilio machaon larvae reared on Angelica keiskei, Oenanthe javanica or Foeniculum vulgare and examined the biological activity of each component. Then, we explored the expression of CYP genes in the midgut of P. machaon larvae and predicted the characteristics of their metabolic system. Results The components that were extracted using hexane, chloroform or methanol were biochemically different between larval frass and the host plants on which the larvae had fed. Furthermore, a fraction obtained from the chloroform extract from frass of A. keiskei-fed larvae specifically inhibited the cell proliferation of the human colon cancer cell line HCT116, whereas fractions obtained from the chloroform extracts of O. javanica- or F. vulgare-fed larval frass did not affect HCT116 cell viability. The metabolites from the chloroform extract from frass of A. keiskei-fed larvae prevented cell proliferation and induced apoptosis in HCT116 cells. Next, we explored the metabolic enzyme candidates in A. keiskei-fed larvae by RNA-seq analysis. We found that the A. keiskei-fed larval midgut might have different characteristics from the O. javanica- or F. vulgare-fed larval metabolic systems, and we found that the CYP6B2 transcript was highly expressed in the A. keiskei-fed larval midgut. Conclusions These findings indicate that P. machaon metabolites might be useful as pharmaceutical agents against human colon cancer subtypes. Importantly, our findings show that it might be possible to use insect metabolic enzymes for the chemical structural conversion of plant-derived compounds with complex structures.